α,α-Difluoro-β-ketophosphonates on a tetraazamacrocyclic platform: Synthesis and inhibitory activity against protein tyrosine phosphatases - Khavrienko, D.I.; Kobzar, O.L.; Shevchuk, M.V.; Romanenko, V.D.; Kobelev, S.M.; Averin, A.D.; Beletskaya, I.P.; Vovk, A.I.; Kukhar, V.P. (Доповіді НАН України, 2014)
The present study offers a new approach for designing inhibitors of protein tyrosine phosphatases. We have synthesized the cyclam derivatives with α,α-difluoro-β-ketophosphonate fragments
covalently attached to tetraazamacrocyclic scaffold, which is known to be of medical interest.
The obtained functionalized macrocycles were evaluated as inhibitors of PTP1B, TC-PTP,
CD45, and other protein tyrosine phosphatases. Запроновано новий пiдхiд до розробки iнгiбiторiв протеїнтирозинфосфатаз. Синтезовано
похiднi цикламу з α,α-дифторо-β-кетофосфонатними фрагментами, ковалентно зв’язаними з тетраазамакроциклiчною платформою. Отриманi функцiоналiзованi макроцикли було
дослiджено як iнгiбiтори PTP1B, TC-PTP, CD45 та iнших протеїнтирозинфосфатаз. Предложен новый поход к разработке ингибиторов протеинтирозинфосфатаз. Синтезированы производные циклама с α,α-дифтор-β-кетофосфонатными фрагментами, ковалентно
связанными с тетраазамакроциклической платформой. Полученные функционализированные макроциклы были изучены в качестве ингибиторов PTP1B, TC-PTP, CD45 и других
протеинтирозинфосфатаз.